Thalidomide alleviated IgA nephropathy through “gut-kidney axis” - Rui-hua Wang; Zhi-jian Zha; Zi-yang Ye; Ya-feng Li (Linchuang shenzangbing zazhi)
Objective Thalidomide has anti-inflammatory, immunomodulatory and renoprotective effects. However, its study in IgA nephropathy has remained scarce. The aim was to explore the role and possible mechanism of thalidomide in IgA nephropathy. Methods MicroRNA-23b-3p-/-（miR-23b-/-） mice were selected as IgA nephropathy model animal. And four groups of model, high-dose thalidomide, low-dose thalidomide and blank control were set up for 8-week intervention. The changes of renal tissue structure, IgA kidney deposition, urinary microalbumin and ileal histomorphology were recorded. The expression of intestinal barrier protein was detected by immunohistochemistry. And enzyme-linked immunosorbent assay（ELISA） was utilized for detecting the levels of interleukin-18 （IL-18） and interleukin-1β （IL-1β） in murine intestine. Western blot was employed for detecting the levels of NLR family, pyrin domain-containing 3 protein（NLRP3） inflammasome related protein, apoptosis-related speck-like protein containing CARD （ASC） and cysteinyl aspartate specific proteinase 1（caspase 1） levels. Results Both low-dose thalidomide and high-dose thalidomide resulted in a reversal of renal histomorphometric destruction in IgA nephropathic mice. There were declines in 24-hour urinary protein quantification in low-dose thalidomide group [（0.5540±0.2454） mg vs （0.2513±0.1238） mg] and high-dose thalidomide group[（0.5540±0.2454） vs （0.3756±0.0992） mg]（P＜0.05）, low-dose thalidomide group[（41.65±15.9） vs （28.21±3.839） μmol/L], high-dose thalidomide group [（41.65±15.93） vs （15.67±5.695） μmol/L]. Blood creatinine dropped and the difference was statistically significant in high-dose thalidomide group（P＜0.05）. Immunofluorescence revealed a decrease in IgA deposition. In model group, ileal tissue morphology was pathologically altered and immunohistochemical stain showed that the levels of intestinal mechanical barrier proteins occludin, ZO-1 and MUC-2 declined （P＜0.05）. After a treatment of low/high-dose thalidomide, ileal tissue alterations were restored and the levels of intestinal mechanical barriers both rebounded （P＜0.05）. As compared with IgA nephropathy mice in low-dose thalidomide group[IL-18（80.52±13.16） vs （39.98±12.41） ng/L, IL-1β（0.9459±0.2347） vs （0.4048±0.2389） ng/L] and high-dose thalidomide group[IL-18（80.52±13.16） vs （49.90±15.07） ng/L, IL-1β （0.9459±0.2347） vs （0.4336±0.1472） ng/L], murine ileum showed lower levels of IL-18 （P＜0.05） and IL-1β（P＜0.05）. Protein immunoblot indicated that thalidomide arrested the activation of NLRP3, ASC and caspase1 in murine ileum and the differences were statistically significant（P＜0.05）. Conclusion Thalidomide alleviates renal disease in mice with IgA nephropathy through suppressing NLRP3 inflammasome and inducing intestinal inflammation for restoring intestinal barrier.